Impact of technology transfer for fennel primary processing on income and employment opportunities for tribal women in district Sirohi (Rajasthan) - L Vyas, R L Bhardwaj, U Nandal, (Journal of Spices and Aromatic Crops, 2014)
Krishi Vigyan Kendra organized a set of need based skill oriented training programmes for selected 500 tribal women (fennel producers) in small groups (25-30 trainees) during last four years (2008 to 2012) with an aim to develop their skills regarding harvesting of umbel at post-mature stage, grading of produce (A, B, C & D grades), drying of fennel in modified shade house made up of local indigenous material, threshing on RCC floor or polyether sheet and packaging in polythene lined bags and marketing of the final produce. The skill oriented trainings had a positive impact on tribal women and about half of the total area (50%) has been transformed in primary processing. By primary processing of fennel, additional employment of about one lakh man days have been generated in district Sirohi. By this intervention, additional monetary returns of around Rs. 29.0 crores have been generated in the district. In the district, trained tribal women are getting Rs. 200-250 day-1 for harvesting and primary processing of fennel, whereas other unskilled women are getting only Rs. 100-150 day-1. This intervention has not only improved the living standards of the rural and tribal households but also increased the socio-economic status by providing self employment opportunities and livelihood security.